2020
DOI: 10.1126/science.aax0860
|View full text |Cite
|
Sign up to set email alerts
|

T cells with dysfunctional mitochondria induce multimorbidity and premature senescence

Abstract: The effect of immunometabolism on age-associated diseases remains uncertain. In this work, we show that T cells with dysfunctional mitochondria owing to mitochondrial transcription factor A (TFAM) deficiency act as accelerators of senescence. In mice, these cells instigate multiple aging-related features, including metabolic, cognitive, physical, and cardiovascular alterations, which together result in premature death. T cell metabolic failure induces the accumulation of circulating cytokines, which resembles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
264
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(297 citation statements)
references
References 31 publications
6
264
0
7
Order By: Relevance
“…T cell mitochondrial dysfunction also accelerates senescence. It was recently demonstrated that Tfam fl/fl Cd4 Cre mice (where mitochondrial transcription factor A (TFAM) is depleted in CD4 + and CD8 + lymphocytes) prematurely died due to multiple age-related changes [ 29 ]. Taken together, the full extent of the molecular pathways involved T c senescence are not completely elucidated.…”
Section: Mechanisms Of T Cell Senescence Inductionmentioning
confidence: 99%
“…T cell mitochondrial dysfunction also accelerates senescence. It was recently demonstrated that Tfam fl/fl Cd4 Cre mice (where mitochondrial transcription factor A (TFAM) is depleted in CD4 + and CD8 + lymphocytes) prematurely died due to multiple age-related changes [ 29 ]. Taken together, the full extent of the molecular pathways involved T c senescence are not completely elucidated.…”
Section: Mechanisms Of T Cell Senescence Inductionmentioning
confidence: 99%
“…45 Compounds that alter the mitochondrial behavior in cells from old donors, or any of the other signatures we modeled in our system, may improve the response to infection in older adults. 46 Altogether, there are many significant differences between young and old viral immune responses as measured by dozens of features in our multi-phenotype aging profile. Normalized averages for features measuring the intensity distribution of mitochondria membrane potential in T cells from old and young donors exposed to rVSV-ΔG-mCherry at a 10× MOI.…”
Section: Dysfunction In the Viral Immune Response In Aging Adultsmentioning
confidence: 98%
“…In particular, they show an age-related decline in mitochondrial function – which could be related to dysfunctional mitophagy [ 36 ]. In fact, mice engineered to have dysfunctional T- cell mitochondria display accelerated senescence and “inflammaging”, highlighting the point that T-cells can determine organismal fitness and lifespan [ 37 ]. This does support data indicating the importance of a healthy T-cell response in defending against the virus [ 38 , 39 ].…”
Section: Mitochondrial Function In Inflammaging and Immunosenescencementioning
confidence: 99%
“…For instance, evidence does indicate a clear role for mitochondria in ageing-related disease and mortality, but not necessarily chronological age [ 156 ]. However, data does suggest that inducing mitochondrial dysfunction alone in T-cells can induce premature senescence, driving “inflammaging” and a tendency towards a cytokine storm [ 37 ]. One well known concept in ageing is the idea of declining organ reserve, which at the molecular level, is related to a loss of excess metabolic capacity – in particular, bioenergetics and mtDNA, as well excess telomere capacity [ 157 ].…”
Section: The Immune System Hormesis and Mitochondriamentioning
confidence: 99%